Preparation, characterization, and antimicrobial activity of xyloglucan-chitosan film from tamarind (tamarind indica L.) seed kernel - Adair, Pornpatu; Sriprom, Pongsert; Narkrugsa, Woatthichai; Phumjan, Lamphung; Manamoongmongkol, Kanjana; Permana, Lasuardi; Assawasaengrat, Pornsawan (My University, 2023)
Xyloglucan from tamarind seed kernel powder and chitosan were prepared using acetic acid as an oxidizing agent to form a xyloglucan-chitosan film. This study evaluated the properties of xyloglucan-chitosan films with different loading ratios of xyloglucan using various analytical tools. The covalent bonds formed by the oxidized xyloglucan and chitosan were confirmed by FTIR analysis. Morphological analysis using SEM indicated the formation of a conventional covalent bond in the xyloglucan-chitosan film. The water vapor transmission rate in the xyloglucan-chitosan film was reduced significantly with increasing xyloglucan ratio. Conversely, the increase in the xyloglucan ratio improved the film's mechanical properties (tensile strength = 1.84 ± 0.06a MPa, elongation at break = 22.47 ± 0.65a %). Furthermore, due to the antimicrobial activity of chitosan, the xyloglucan-chitosan film exhibits intense antimicrobial activity. Therefore, the xyloglucan-chitosan film demonstrated good properties for biodegradable food packaging.
Keywords: Chitosan; Tamarind seed kernel powder; Xyloglucan; Xyloglucan-chitosan film